Investigations into inflammation and nerve regeneration in a human model system of neuropathic pain - Sandy-Hindmarch, O (2020)
Neuropathic pain is a serious and debilitating disease affecting a large proportion of the population. The disease is caused by direct damage to the nervous system and is often chronic in nature. Neuropathic pain is typically poorly treated, with patients often experiencing inadequate relief from symptoms. Part of this issue stems from ineffective treatment options while a lack of understanding of the disease pathology also presents as a major issue.